The Utility of Alvarado Score, RIPASA Score, NLR, and PLR for Predicting Acute Appendicitis - Halim, Sanjaya; Parinding, Imanuel Taba (Fakultas Kedokteran Universitas Lambung Mangkurat, 2024)
Acute appendicitis requires fast and precise diagnosis. Delay in diagnosis will increase the risk of complications, as well as morbidity and mortality. Modalities such as ultrasound or CT scan are not always available. The purpose of this study was to analyze the Alvarado score, RIPASA score, NLR and PLR to predict the diagnosis of acute appendicitis in a type C Hospital. This research is an observational analytic study using a cross-sectional approach, from medical records. The diagnosis is made by surgeon based on clinical, laboratory, imaging findings, then confirmed by surgery and histopathology. From a total of 32 patients, there were 21 patients (66%) with a final diagnosis of acute appendicitis, and 11 patients (34%) with a final diagnosis of non-acute appendicitis. Alvarado score ³7 has an AUC value of 81.6%, with a sensitivity of 57.14%, a specificity of 81.82%. RIPASA score ³7.5 has an AUC value of 84.6% with a sensitivity of 80.95%, a specificity of 81.82%. NLR with a cut-off value of >4.49 can be used to detect acute appendicitis, and a cut-off value of >9.13 for perforated appendicitis. PLR with a cut-off value of >172.2 can be used to detect perforated appendicitis.